Nanosponge: A promising and intriguing strategy in medical and pharmaceutical Science - Akash Garg; Wen-Cheng Lai; Himansu Chopra; Rutvi Agrawal; Talever Singh; Ramkumar Chaudhary; Braj Nandan Dubey (Heliyon, 2024)
The complicated chemical reactions involved in the production of the newer drug delivery systems have mainly impeded efforts to build successful targeted drug delivery systems for a prolonged duration of time. Nanosponges, a recently created colloidal system, have the potential to overcome issues with medication toxicity, decreased bioavailability, and drug release over a wide area because they can be modified to work with both hydrophilic and hydrophobic types of drugs. Nanosponges are small sized with a three-dimensional network having a porous cavity. They can be prepared easily by crosslinking cyclodextrins with different compounds. Due to Cyclodextrin's outstanding biocompatibility, stability, and safety, a number of Cyclodextrin-based drug delivery systems have been developed promptly. The nanosponge drug delivery system possesses various applications in various ailments such as cancer, autoimmune diseases, theranostic applications, enhanced bioavailability, stability, etc. This review elaborates on benefits and drawbacks, preparation techniques, factors affecting their preparation, characterization techniques, applications, and most current developments in nanosponges.